Experimental Study of the Effect of Confining on the Development of Fire in a Closed Compartment - Fidel Meskeoule Vondou; Claude Valery Ngayihi Abbe; Justin Tégawendé Zaida; Philippe Onguene Mvogo; Ruben Mouangue (Journal of Combustion)
Backdraft is a complex phenomenon which occurs during cases of confined fires. It appears by a fast deflagration which occurs after the introduction of oxygen into a compartment filled with hot gases rich in unburned combustible vapor. Practically, this situation could occur at the time of intervention of firemen who break the door or when a window breaks under the action of thermal stresses. Based on a strong experimental campaign, the present paper aimed to make a quantitative investigation of the effect of confining on a totally closed fire. With this focus, fire tests were carried out in a completely closed room of dimensions 1.20 m × 1.20 m × 1.02 m, with five sources of fire of different heat release rates. The same fire sources were also tested in a free atmosphere in order to get reference data. After a statistical study of data, a comparative analysis between both results has been done. Its outcome is that confining has a major impact on the quality of combustion and on the fire duration. More precisely, it has been noticed comparatively to fire tests in free atmosphere that confining increases the fire duration by 14.85 percent while it decreases the heat release rate by 21.72 percent.